Efficacy of (S)-lacosamide in preclinical models of cephalic pain. (July 2016) - Moutal, Aubin; Eyde, Nathan; Telemi, Edwin; Park, Ki Duk; Xie, Jennifer Y.; Dodick, David W.; Porreca, Frank; Khanna, Rajesh
Abstract : Abstract: Migraine is one of the world's most common neurological disorders. Current acute migraine treatments have suboptimal efficacy, and new therapeutic options are needed. Approaches targeting calcitonin gene related peptide (CGRP) signaling are clinically effective, but small molecule antagonists have not been advanced because of toxicity. In this study, we explored the axonal growth/specification collapsin response mediator protein 2 (CRMP2) as a novel "druggable" target for inhibiting CGRP release and for potential relevance for treatment of migraine pain. Collapsin response mediator protein 2 has been demonstrated to regulate N-type voltage-gated Ca 2+ channel activity and Ca 2+ -dependent CGRP release in sensory neurons. The coexpression of CRMP2 with N-type voltage-gated Ca 2+ channel and CGRP in trigeminal ganglia (TGs) sensory neurons suggested the possibility of a novel approach to regulate CGRP release in the trigeminal system. Screening protocols surprisingly revealed that ( S )-lacosamide (( S )-LCM), an inactive analog of the clinically approved small molecule antiepileptic drug ( R )-lacosamide (Vimpat), inhibited CRMP2 phosphorylation by cyclin-dependent kinase 5 in rat TG slices and decreased depolarization-evoked Ca 2+ influx in TG cells in culture. ( S )-LCM significantly blocked capsaicin-evoked CGRP release from dural nerve terminals in the rat in ex vivo cranial cup preparation. Additionally, cephalic and extracephalic cutaneous allodynia induced in rats by activation of dural nociceptors with a cocktail of inflammatory mediators, was inhibited by oral administration of ( S )-LCM. The confirmation of CRMP2 as an upstream mediator of CGRP release, together with the brain penetrance of this molecule suggests ( S )-LCM as a potential therapy for acute migraine.